Partitioning the relative contribution of one-phase and two-phase seed dispersal when evaluating seed dispersal effectiveness - Culot, Laurence [UNESP]; Huynen, Marie-Claude; Heymann, Eckhard W. (Wiley-Blackwell, 2015)
Seed dispersal effectiveness (SDE) is a conceptual framework that aims at quantifying the contribution of seed dispersal vectors to plant fitness. While it is well recognized that diplochorous dispersal systems, characterized by two successive dispersal steps performed by two different vectors (Phase I=primary seed dispersal and Phase II=secondary seed dispersal) which are common in temperate and tropical regions, little attention has been given to distinguishing the relative contribution of one-phase and two-phase dispersal to overall SDE. This conceptual gap probably results from the lack of a clear methodology to include Phase II dispersal into the calculation of SDE and to quantify its relative contribution. We propose a method to evaluate the relative contribution of one-phase and two-phase dispersal to SDE and determine whether two seed dispersers are better than one. To do so, we used the SDE landscape and an extension of the SDE landscape, the Phase II effect landscape, which measures the direction and magnitude of the Phase II dispersal effect on overall SDE. We used simulated and empirical data from a diplochorous dispersal system in the Peruvian Amazon to illustrate this new approach. Our approach provides the relative contribution of one-phase SDE (SDE1) and two-phase SDE (SDE2) to overall SDE and quantifies how much SDE changes with the addition of Phase II dispersal. Considering that the seed dispersal process is context dependent so that Phase II depends on Phase I, we predict the possible range of variation of SDE according to the variation of the probability of Phase II dispersal. In our specific study system composed of two primate species as primary dispersal vectors and different species of dung beetles as secondary dispersal vectors, the relative contribution of SDE1 and SDE2 to overall SDE varied between plant species. We discuss the context dependency of the Phase II dispersal and the potential applications of our approach. This extension to the conceptual framework of SDE enables quantitative evaluation of the effect of Phase II dispersal on plant fitness and can be easily adapted to other biotic and/or abiotic diplochorous dispersal systems.
Keywords: Diplochory; Primary seed dispersal; Secondary seed dispersal; Seed dispersal effectiveness; Seed burial; Seed survival